Discovery and application of insertion-deletion (INDEL) polymorphisms for QTL mapping of early life-history traits in Atlantic salmon - Vasemägi, Anti (BioMed Central, 2010)
BACKGROUND: For decades, linkage mapping has been one of the most powerful and widely used approaches for elucidating the genetic architecture of phenotypic traits of medical, agricultural and evolutionary importance. However, successful mapping of Mendelian and quantitative phenotypic traits depends critically on the availability of fast and preferably high-throughput genotyping platforms. Several array-based single nucleotide polymorphism (SNP) genotyping platforms have been developed for genetic model organisms during recent years but most of these methods become prohibitively expensive for screening large numbers of individuals. Therefore, inexpensive, simple and flexible genotyping solutions that enable rapid screening of intermediate numbers of loci (~75-300) in hundreds to thousands of individuals are still needed for QTL mapping applications in a broad range of organisms. RESULTS: Here we describe the discovery of and application of insertion-deletion (INDEL) polymorphisms for cost-efficient medium throughput genotyping that enables analysis of >75 loci in a single automated sequencer electrophoresis column with standard laboratory equipment. Genotyping of INDELs requires low start-up costs, includes few standard sample handling steps and is applicable to a broad range of species for which expressed sequence tag (EST) collections are available. As a proof of principle, we generated a partial INDEL linkage map in Atlantic salmon (Salmo salar) and rapidly identified a number of quantitative trait loci (QTLs) affecting early life-history traits that are expected to have important fitness consequences in the natural environment. CONCLUSIONS: The INDEL genotyping enabled fast coarse-mapping of chromosomal regions containing QTL, thus providing an efficient means for characterization of genetic architecture in multiple crosses and large pedigrees. This enables not only the discovery of larger number of QTLs with relatively smaller phenotypic effect but also provides a cost-effective means for evaluation of the frequency of segregating QTLs in outbred populations which is important for further understanding how genetic variation underlying phenotypic traits is maintained in the wild.